Missed treasures of the Holy Spirit: distinctive new testament pneumatologies - Corley, Jeremy; Rogers, Jessie (Catholic biblical quarterly imprints, 2024)
"In this volume on the Holy Spirit, "missed treasures" designates the rich pneumatologies in the New Testament books beyond Paul, John, and Luke-Acts. Depictions of the Holy Spirit in Matthew, the Letter of James, Revelation, and other books are analyzed and incorporated into the theological tapestry of New Testament thought. Another unique feature of this volume is its focus on the numinous presence of God in the sweep of Israel's history; there are chapters on the Septuagint, the Dead Sea Scrolls, and the Wisdom of Solomon that trace Christian pneumatology back to its source, the Hebrew Scriptures. In short, this volume expands the scholarly conversation exponentially as it explores a complement of texts spanning the New Testament and reaching back into the Hebrew Scriptures. A lucid guide to the distinctive pneumatologies of the New Testament, this collection is must reading for all who would engage the dialogue between scriptural study and systematic theology"--